2017
DOI: 10.1111/spc3.12369
|View full text |Cite
|
Sign up to set email alerts
|

Becoming part of me: Examining when objects, thoughts, goals, and people become fused with the self‐concept

Abstract: Fusion refers to the sense that a construct is integrated into the self-concept. When a person feels fused with a construct, there is a perceived "oneness" with the construct, and as a result, the construct is treated as an extension of the self. This concept of fusion has been explored across a wide range of constructs and within a number of subfields in psychology. The goal of this article is to provide a comprehensive view of the fusion process and to connect these disparate areas of literature underneath a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
(179 reference statements)
0
4
0
2
Order By: Relevance
“…The extent of Emily’s goal internalisation – evidenced by greater goal investments and goal achievements is indicative of higher goal fusion. This finding illustrates how the goals that we undertake are more than something we strive for, but are a part of who we are (Hatvany et al , 2018), minimising the degree of congruence between one’s “ideal” and one’s current self. The findings of this study thus provide support to the fact that high integration of personal goals with one’s self (goal fusion) can shape behaviour and goal-relevant cognitions.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The extent of Emily’s goal internalisation – evidenced by greater goal investments and goal achievements is indicative of higher goal fusion. This finding illustrates how the goals that we undertake are more than something we strive for, but are a part of who we are (Hatvany et al , 2018), minimising the degree of congruence between one’s “ideal” and one’s current self. The findings of this study thus provide support to the fact that high integration of personal goals with one’s self (goal fusion) can shape behaviour and goal-relevant cognitions.…”
Section: Discussionmentioning
confidence: 81%
“…They further argue that the more a goal is perceived to be fused with the self, the more it is included within the knowledge structures of the self. For this reason, when goal fusion is high, the goal is no longer something the person does, but rather it is who they are (Hatvany et al , 2018). Interestingly, while goal setting has been used extensively in higher education research to support student learning, research into the use of goal setting and self-referent mechanism for teacher development is still noticeably absent (Camp, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los indicadores de esta dimensión aportan evidencia concordante con la premisa de que, si bien la claridad no es equivalente con el contenido del autoconcepto, sí se deriva en parte de las autodescripciones de la persona (Slotter et al, 2015). Los objetivos son más que algo que se desea alcanzar: son un aspecto fundamental a través del cual las personas definen quiénes son, ya que proporcionan información acerca de sus capacidades, habilidades, intereses y características (Hatvany et al, 2017). Por ende, el fracaso en el alcance de los objetivos puede llevar al individuo a cuestionarse "¿quién soy ahora?…”
Section: Discussionunclassified
“…Por ejemplo, se observó que los sucesos de vida determinan en particular el sentido de estabilidad (Holm y Kirkegaard, 2018). Además, tener metas bien establecidas mejora la seguridad en el autoconcepto porque éstas reflejan aspectos esenciales de cómo se define una persona (como sus intereses y características) (Hatvany et al, 2017). En cambio, se halló que la congruencia se vincula con la manera de comportarse, describirse y con la confirmación del autoconcepto por parte de otros (e.g.…”
Section: Tabla De Contenidounclassified
“…In a related study, Briñol et al 30 reported that writing down negative thoughts about a Mediterranean diet on a piece of paper and disposing of the paper in a trash can result in lower negative (more positive) evaluations of the diet, compared to a group that kept the paper in a booklet. These attitude changes may derive from the cognitive fusion that people often fuse with physical objects, such as jewellery, cars, and family heirlooms 31 . Such fused objects are valued more and are less likely to be abandoned because doing so means losing a part of themselves 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%